Effects of Spartina alterniflora invasion on spatial and temporal variations of total sulfur and inorganic sulfur fractions in sediments of salt marsh in the Min River estuary, southeast China. (June 2020) - He, Tao; Sun, Zhigao; Hu, Xingyun; Chen, Bingbing; Wang, Hua; Wang, Jie
Graphical abstract: Highlights: Spartina alterniflora invasion greatly altered the variations of TS and IS fractions in sediments. Variations of sediment texture caused by plant invasion showed great effects on IS fractions. Spartina alterniflora invasion greatly increased the contents of TS and IS fractions in sediments. Increased S stocks was an effective strategy for Spartina alterniflora to invade Cyperus malaccensis. Strong tolerance of Spartina alterniflora to high levels of sulfide increased its competitiveness. Abstract: To investigate the effects of Spartina alterniflora invasion on spatial and temporal variations of sulfur in marsh sediments, the levels of total sulfur (TS) and inorganic sulfur (IS) fractions (Water-Soluble-S, W-S-S; Adsorbed-S, A-S; HCl-Soluble-S, H-S-S; and HCl-Volatile-S, H-V-S) were determined in Cyperus compressus marsh (before invasion, BI), S. alterniflora - C. compressus marsh (during invasion, DI) and S. alterniflora marsh (after invasion, AI) in the Min River estuary (Southeast China) by space-for-time substitution method. Results showed that the variations of sediment texture caused by S. alterniflora invasion showed great influences on the levels of TS and IS fractions in sediments at DI and AI stages. Compared with BI stage, the mean values of TS (g·kg −1 ) at AI and DI stages increased by 21.36% and 20.57%, while those of TIS (mg·kg −1 ) increased by 24.84% and 20.59%, respectively. Over all sampling seasons, significantly higher contents of W-S-S, A-S and H-S-S in sediments at AI or DI stages were observed compared to BI stage ( p < 0.05). However, only the contents of H-V-S in sediments at DI and AI stage during summer or autumn were significantly higher than those at BI stage ( p < 0.05). Moreover, compared with BI stage, the average stocks (g·m −2 ) of TS and TIS in sediments of all sampling seasons at AI and DI stages increased by 19.84%, 25.20% and 23.58%, 22.78%, whereas the values of W-S-S, A-S, H-S-S and H-V-S increased by 20.49%, 42.53%, 22.23%, 5.28% and 14.80%, 38.48%, 24.15%, 6.47%, respectively. These results implied that, compared to C. malaccensis, the increased S stocks in sediments might be an effective strategy for S. alterniflora to successfully invade C. malaccensis in the Min River estuary and the strong tolerance of S. alterniflora to high levels of sulfide might be more favorable for boosting its competitiveness.